Navigational Rights for Warships in the Northwest and Northeast Passages - Handeland, Ingrid (Arctic Review on Law and Politics, 2022)
Climate change has renewed the debate about shipping in the Arctic due to an expected reduction of ice in these sea lanes. Because of the Arctic slowly opening, allowing for more activity, navigational rights for ships have caught the attention of the world once again, including those of warships. Through analysing the navigational regime for warships in the Northwest and Northeast Passages, this article aims to introduce the different rules for navigation and the consequences for maritime operations in the Arctic, including the right to overflight. The United Nations Convention on the Law of the Sea provides navigational rights for warships and overflight in peace time operations, but the matter of which navigation rules should apply in the passages is under debate. Based on an analysis of the Convention, case law, legal theory and customary law, the article aims to shed light on different interpretations of the legal regimes of navigation in the passages and which rules should apply to warships and overflight in the future.